2016
DOI: 10.4103/0975-1475.195121
|View full text |Cite
|
Sign up to set email alerts
|

Cementum as an age determinant: A forensic view

Abstract: Context:Forensic age estimation (FAE) defines an expertise in forensic medicine, which aims to define in the most accurate way to determine the unknown chronological age of the person involved in judicial or legal proceedings. Dental cementum is a vital tissue which demonstrates continuous apposition throughout the life of the tooth. This appositional changes of cementum helps in approximation of age inforensic investigations.Aims:To correlate age by measuring the overlap or coronal migration of thecementum at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In contradictory to this, a study done by Balwant et al in 2006 andRaju et al in 2016 in erupted mandibular third molar teeth, found no significant correlation between age and coronal displacement of cementum in erupted teeth because erupted teeth were found to be directly exposed to external environmental factors (Rai et al, 2006;Raju et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…In contradictory to this, a study done by Balwant et al in 2006 andRaju et al in 2016 in erupted mandibular third molar teeth, found no significant correlation between age and coronal displacement of cementum in erupted teeth because erupted teeth were found to be directly exposed to external environmental factors (Rai et al, 2006;Raju et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…In these groups the adults presented a significantly higher volume of PDL region compared to the young. This is possibly due to cementum deposition occurring with age [ 22 ] causing an increase in the mesio-distal aspect of the adult teeth in the apical area. Buco-lingual cementum deposition does not affect our result because we analyzed the same number of slices for all teeth on the buco-lingual aspect.…”
Section: Resultsmentioning
confidence: 99%
“…Cementochronology is a potent method for directly evaluating the chronological age and determining the season at death [ 48 ]. The apical areas of cementum are thicker than parts at the CEJ, and its shape and texture are stable within an individual's life [ 49 ]. The underlying mechanism is the racemization reaction of aspartic acid in a constant manner [ 50 ] that produces a connective tissue in the form of incremental layers surrounding tooth roots and creates an appearance of concentric lines [ 51 ].…”
Section: Dental Parameters Used In Sex and Age Estimationmentioning
confidence: 99%